The GH/IGF-1 axis in obesity: pathophysiology and therapeutic considerations - Berryman, Darlene E.; Glad, Camilla A. M.; List, Edward O.; Johannsson, Gudmundur (Nature reviews. Endocrinology, 2013)
Administration of recombinant human growth hormone (GH) or activation of endogenous GH production exhibits great potential to influence the onset and metabolic consequences of obesity; however, the clinical use of GH is not without controversy. This Review provides an introduction to the role of GH in obesity and summarizes clinical and preclinical data that describe how GH can influence the obese state. Obesity has become one of the most common medical problems in developed countries, and this disorder is associated with high incidences of hypertension, dyslipidaemia, cardiovascular disease, type 2 diabetes mellitus and specific cancers. Growth hormone (GH) stimulates the production of insulin-like growth factor 1 in most tissues, and together GH and insulin-like growth factor 1 exert powerful collective actions on fat, protein and glucose metabolism. Clinical trials assessing the effects of GH treatment in patients with obesity have shown consistent reductions in total adipose tissue mass, in particular abdominal and visceral adipose tissue depots. Moreover, studies in patients with abdominal obesity demonstrate a marked effect of GH therapy on body composition and on lipid and glucose homeostasis. Therefore, administration of recombinant human GH or activation of endogenous GH production has great potential to influence the onset and metabolic consequences of obesity. However, the clinical use of GH is not without controversy, given conflicting results regarding its effects on glucose metabolism. This Review provides an introduction to the role of GH in obesity and summarizes clinical and preclinical data that describe how GH can influence the obese state. Key Points Growth hormone (GH) and insulin-like growth factor 1 (IGF-1) signalling plays a major part in fuel metabolism and in the regulation of body composition Obesity, particularly abdominal obesity, exerts a strong negative effect on the spontaneous pulsatile secretion of GH, which has been associated with adverse metabolic complications GH administration in individuals with abdominal obesity reduces visceral and total body adipose tissue mass, as well as levels of total and LDL cholesterol Increasing the endogenous pulsatile GH secretion in individuals with obesity has metabolic effects similar to those obtained by the administration of exogenous GH but potentially with less adverse effects on glucose metabolism Mouse models with altered GH signalling provide a useful means for a comparative analysis of GH action in obesity The role of the GH/IGF-1 axis in modifying obesity must be assessed in light of newly emerging data that highlight the complexity of adipose tissue